The Role of Language Severity and Education in Explaining Performance on Object and Action Naming in Primary Progressive Aphasia - Riello, Marianna; Faria, Andreia V.; Ficek, Bronte; Webster, Kimberly; Onyike, Chiadi U.; Desmond, John; Frangakis, Constantine; Tsapkini, Kyrana (Frontiers in Aging Neuroscience, 2018)
BACKGROUND: PPA is a complex syndrome and several types of data, clinical, neuropsychological and imaging are needed for its diagnosis and subtyping. One of the main deficits in PPA is naming. OBJECTIVE: In this study, we probed the impact of brain volumes as well as clinical and demographic variables in predicting object and action naming performance in a cohort of patients with primary progressive aphasia (PPA). METHODS: Thirty-nine participants underwent magnetic resonance imaging (MRI) for volumetric analysis and a complete neuropsychological examination including standardized tests of object and action naming. We used stepwise regression models to compare the effect of brain volumes in the areas of the language network (volumetric-only model) to the additional effects of demographic and clinical features of PPA (all-inclusive model) on naming objects and actions. RESULTS: The all-inclusive model was the best-fit model that explained the largest amount of variance in both object and action naming, emphasizing the role of temporal areas in naming performance independent from clinical severity. CONCLUSION: Brain volume measurements alone do not provide adequate explanations for performance in either object or action naming in PPA. Clinical factors, such as severity, as well as demographic factors, such as education, need to be considered in conjunction with brain volumes in PPA. The present study emphasizes the complexity of PPA as a syndrome and gives an example of how volumetric, clinical and demographic factors may interact in determining naming performance/deterioration.